1991
DOI: 10.1111/j.1464-410x.1991.tb15074.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Accuracy of Linear Array Transrectal Ultrasound in Measurement of the Prostate

Abstract: In 61 prostate autopsy specimens, linear array transrectal ultrasound and electronic vernier calipers were used to measure 3 maximal diameters along the longitudinal, anterior-posterior and transverse axes. The results were comparable. We assessed the reliability of empirical formulae, derived from various combinations of these 3 diameters, for the prediction of prostatic volume and weight. Formulae using all 3 diameters were accurate. The combination of longitudinal and anterior-posterior diameters, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These authors, using the resected prostate as the "gold standard", found that their length measurement had a poor correlation with actual length, while the APD and TD measurements correlated strongly with the actual measurements. In a study of 61 autopsy prostates, Yip et al (1991) found that while all 3 ultrasonic measurements correlated strongly with caliper measurements, length had the weakest correlation with the actual measurement and with prostate volume. In the present study, L had a stronger correlation with volume than the TD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These authors, using the resected prostate as the "gold standard", found that their length measurement had a poor correlation with actual length, while the APD and TD measurements correlated strongly with the actual measurements. In a study of 61 autopsy prostates, Yip et al (1991) found that while all 3 ultrasonic measurements correlated strongly with caliper measurements, length had the weakest correlation with the actual measurement and with prostate volume. In the present study, L had a stronger correlation with volume than the TD.…”
Section: Discussionmentioning
confidence: 95%
“…The accuracy and simplicity of the diameter method of volume estimation make it practical in the busy clinical situation. Studies on the diameter method are flawed by vague methodology regarding length measurement (Littrup et al, 1991a and b;Yip et al, 1991), which can be difficult because the apex of the prostate is frequently obscured by the echopenic shadow of the external sphincter. In a study by Terris and Stamey (1991), length was measured from the apex to the junction of the central zone and seminal vesicle, which is an easily identifiable landmark.…”
Section: Discussionmentioning
confidence: 99%
“…The single most common cause for variation of total prostatic volume between examiners is likely selection of precise lower and upper landmarks in the mid-sagittal plane while measuring length [5,28]. Common errors include incorrect identification of the inferior boundary of the apex as the caudal landmark, inconsistent identification of the cranial landmark, making measurements in a parasagittal (rather than mid-sagittal) plane, and measuring from the anterior or posterior prostatic base to apex.…”
Section: Discussionmentioning
confidence: 99%
“…Collins et al [10] found that for experienced operators the variability could be largely explained by definitions of the length measurement, whilst others have found equal variability in definitions of all dimensions [8]. Others comparing TRUS with actual specimens found similar discrepancies attributable to measurement and interpretation [11,12]. Issues relating to equipment specifications (hardware and software), acquisition technique, interpretation and recording are also likely to contribute to variability.…”
Section: Introductionmentioning
confidence: 99%